Recognition and management of sepsis: the nurse's role. (26th November 2020) - Bleakley, Greg; Cole, Mark
Abstract : Caring for a patient with suspected sepsis is a challenging nursing role. Early recognition and appropriate management of a patient with sepsis saves lives. Nurses play a fundamental role in detecting changes in physiological observations that could indicate the onset of sepsis. Additionally, an awareness of the pathophysiology of sepsis allows the nurse to better understand how rapid intervention prevents the onset of septic shock. Furthermore, knowledge and use of clinical guidelines and sepsis screening tools are established methods to help reduce patient mortality. Nurse familiarity with 'red flag' criteria for sepsis and thorough completion of early warning scores facilitate earlier recognition and time critical intervention. Delivery of the 'sepsis six' within 1 hour of suspected sepsis saves lives.